Middle Assyrian seal motifs from Tell Fekheriye (Syria) - Bonatz, Dominik 1966- (Tell Fekheriye Excavation Reports, 2021)
Despite ongoing interest in Middle Assyrian glyptic art, the publications of Middle Assyrian seals and seal impressions from excavated sites in the Near East are very rare. The book is the first to offer a comprehensive study on the seal corpus from an archaeological site historically located in the western territory of the Middle Assyrian state. The seal impressions and few original seals, which were found during the excavations in Tell Fekheriye (Syria), substantially add to our understanding of the iconographic repertory and the use of seals in the Middle Assyrian period. The corpus dates to the reigns of the Assyrian kings Shalmaneser I and Tukulti-Ninurta I in the 13th century B.C. It documents practices of governance and administration in the growing Middle Assyrian Empire, points to activities of high-ranking Assyrian officials and unfolds the pictorial reality of political and ideological intensions. While finding detailed information on unpublished materials, their archaeological contexts and interpretations, the reader is also invited to follow a discourse on art, state and society for which the Middle Assyrian seal motifs from Tell Fekheriye provide an excellent case study